Penyuluhan Hukum Tentang Perlindungan Konsumen Terhadap Penggunaan Bahan Tambahan Pangan - Theresia Loize Pesulima; Sarah Selfina Kuahaty; Sabri Fataruba; Ronald Fadly Sopamena (AIWADTHU: Jurnal Pengabdian Hukum, 2022)
Introduction: In running their business, business actors, especially business actors engaged in the culinary field, try to make the food or drinks they serve attract consumers' intentions to buy. Not infrequently, in order to beautify the appearance of food, they use food additives (BTP).Purposes of Devotion: This service aims to make the Toisapu village community better understand their rights as consumers, especially for the use of food additives (BTP) in the food and beverage products they consume. Method of Devotion: This counseling is carried out by presenting material by resource persons and followed by discussion and question and answer from the community.Results of the Devotion: The Toisapu village community, the majority of which work as fishermen, farmers and motorcycle taxi drivers, are consumers who consume food and beverage products that contain BTP, so it is necessary to understand the residents of Toisapu village as consumers who have rights guaranteed by law. In addition, as consumers, the residents of Toisapu village must be careful and selective in choosing the food and beverage products they consume.